Patient Safety Culture from Rahnemon Hospital Nurses' Perspective - Fatemeh Pourshareiati; Mohammad Amrollahi (Shahid Sadoughi University of Medical Sciences, 2017)
Introduction: Improving patients' safety is one of the main objectives of health systems, so it is essential to examine the patients' safety culture among nurses. The aim of the study was to identify nurses' perceptions of patients' safety culture in Rahnemon Hospital. Methods: This descriptive- analytic study was carried out with 142 nurses in Rahnemon hospital, Yazd province, Iran. Data were collected by using the Hospital Survey of Patient Safety Culture questionnaire (HSOPSC) that includes 42 questions and 12 dimensions. Data were then analyzed by descriptive statistics, independent t-test, and ANOVA. Results: The highest and lowest mean and standard deviation scores were respectively related to dimensions of organizational learning (3.92±0.30) and information exchange and transfer (2.23±0.51). According to results achieved through independent t-test, there was a significant relationship between nurses' gender and patients' safety culture. In addition, according to the ANOVA test there was a significant relationship between nurses' work experience and patients' safety culture. Conclusion: According to the results, patients' safety culture was in average level. Finally, development of a reporting system for staffs to report errors and adjustment of nursing in units according to workload are suggested.